Global research profile on monkeypox-related literature (1962–2022): A bibliometric analysis - Sofyantoro, Fajar; Kusuma, Hendrix I.; Vento, Sandro; Rademaker, Marius; Frediansyah, Andri (Narra Sains Indonesia, 2022)
The recent monkeypox or mpox outbreak has been a global concern. The present study evaluated the global research outputs, research trends, and topics of published research on monkeypox using a bibliometric approach. The Scopus database was searched for terms associated with